Metal-on-Metal Compared With Metal-on-Polyethylene: The Effect on Trunnion Corrosion in Total Hip Arthroplasty - Lanting, Brent A.; Teeter, Matthew G.; Howard, James L.; MacDonald, Steven J.; Van Citters, Douglas W. (The Journal of arthroplasty, 2017)
Trunnion tribocorrosion in total hip arthroplasties is concerning, but retrieval studies often are subjective or lack comparison groups. Quantitative comparisons of clinically relevant implants are required. The purpose of this investigation was to evaluate material loss in metal-on-metal (MoM) and metal-on-polyethylene (MoP) total hip articulations while controlling for trunnion design and head size. The 166 retrieved femoral heads from 2 manufacturers were analyzed. Four cohorts based on head size, trunnion design, manufacturer, and articulation type (MoM vs MoP) were created. Corrosion was measured by a coordinate measurement machine, and material loss was assessed (MATLAB). Retrieved femoral heads from MoP articulations had 5 times less trunnion material loss than MoM articulations, on average, for both manufacturers. There was no difference in material loss between large modular head (>40 mm) and 36-mm MoM hip trunnion. Implants with a material loss above the detectable limit demonstrated a correlation with time in vivo only in MoP articulations. Retrieved femoral heads from MoP bearing couples had a lower magnitude of material loss than MoM couples, independent of head diameter. A time in vivo effect was only seen in MoP bearings.